Characteristics of benthic macroinvertebrate communities in a typical high sediment-loaded river in China - Shiyun Chi; Jinxiu Zheng; Jun Hu; Ming Li; Mi Wei; Yuping Su; Juxiang Hu (Journal of Freshwater Ecology)
To date, the knowledge of benthic macroinvertebrates in the upper reaches of the Jinsha River remains quite limited compared to other rivers in China due to the difficulty of sampling and special geographical environment. In this study, benthic macroinvertebrates in the upper reaches of the Jinsha River were investigated to address the knowledge gap. The results showed that dipterans dominated the communities, followed by amphipods and EPT taxa. The density, biomass and biodiversity were at a low level. As a high sediment-loaded river, unlike the Yellow River and the Wei River, oligochaetes are not commonly found in the upper reaches of the Jinsha River, and no mollusks were collected. The results of db-RDA showed that some natural factors influenced the spatial distribution of benthic macroinvertebrates in both dry and wet seasons, but during the flood season (summer and autumn), nitrogen and phosphorus became important factors due to severe soil erosion and high sediment loads in the water. The sections between above Batang and below Batang have obviously different substrates, resulting in the significantly different species composition and functional feeding groups. Moreover, higher habitat diversity can lead to higher benthic macroinvertebrate diversity after comparing the substrate types of the two sections. We consider that the unstable habitat conditions in the upper reaches of the Jinsha River are not conducive to completing the entire life cycle of benthic macroinvertebrates within a localized small habitat, and the communities are likely influenced more by seasonal contributions from populations in tributaries. Considering the impact of the existing cascade hydropower stations in the middle and lower reaches, and the realistic and potential impacts expected from the planned cascade hydropower stations in the upper reaches, it is imperative to prioritize the conservation of the tributaries along both banks of the upper Jinsha River. This enhanced conservation effort aims to preserve the diversity and integrity of benthic macroinvertebrates, which is of great significance in providing reliable food sources for the rare cold-water fish species and ensuring the safety of the aquatic ecosystem in the region.